Insights into microbial community structure and function from a shallow, simulated CO2‐leakage aquifer demonstrate microbial selection and adaptation. Issue 3 (5th August 2018) - Gulliver, Djuna; Lipus, Daniel; Ross, Daniel; Bibby, Kyle
Summary: Geological carbon storage is likely to be a part of a comprehensive strategy to minimize the atmospheric release of carbon dioxide (CO2 ), raising concerns that injected CO2 will leak into overlying freshwater aquifers. CO2(aq) leakage may impact the dominant microbial community responsible for important ecosystem functions such as nutrient cycling, metal cycling and carbon conversion. Here, we examined the impact of an experimental in situ CO2 ‐leakage on a freshwater aquifer microbial community. High‐throughput 16S rRNA gene sequencing demonstrated lower microbial diversity in freshwater wells with CO2 concentrations above 1.15 g l −1 . Metagenomic sequencing and population genome binning were used to evaluate the metabolic potential of microbial populations across four CO2 exposed samples and one control sample. Population genome binning resulted in the recovery and annotation of three metagenome assembled genomes (MAGs). Two of the MAGs, most closely related to Curvibacter and Sulfuricurvum, had the functional capacity for CO2 utilization via carbon fixation coupled to sulfur and iron oxidation. The third draft genome was an Archaea, most closely related to Methanoregula, characterized by the metabolic potential for methanogenesis. Together, these findings show that CO2 leakage in a freshwater aquifer poses a strong selection, driving both microbial community structure and metabolic function.